Social justice and its role in achieving economic security in the Libyan society (Journal of Human Sciences, 2023)
The crimes of defamation and cyber extortion that are published on the Internet are among the biggest manifestations of moral corruption in society today, and despite the difference in determining an acceptable definition of the materials being published, there is a factor that can be relied upon to determine their meaning, which is that these crimes include content that indicates a violation of sanctities and values morality in society. Accordingly, this study aims to know the repercussions of moral corruption on the value system in Libyan society, and to know the true goals behind what is published in the pages of defamation and cyber extortion, and to reveal the psychological and social effects of defamation and cyber extortion crimes on the values of society. To achieve this goal, the concepts related to moral corruption and crimes of defamation and cyber extortion were studied, as well as theoretical trends in the interpretation of crimes of defamation and electronic extortion as a manifestation of moral corruption. The study relied in its methodology on the descriptive approach. Thus, the main question that revolves around the study problem is: What are the implications of moral corruption on the value system in Libyan society?The questions of the study were answered through the results of the exploratory study of the pages of electronic defamation and extortion that were identified in  three  pages, where the study concluded that the Libyan society in general  and the society of Sabha city  in particular, is a conservative society that still adheres to the agreed-upon values and standards and the percentage of moral corruption is not great, and finally the paper suggests some  recommendations that concern with the  preventive treatment to alleviate this problem and prevent its occurrence in the Libyan society.